2020
DOI: 10.1080/24725625.2020.1808304
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis colitis in a patient positive for human T-cell leukaemia virus with rheumatoid arthritis during an anti-rheumatic therapy: a case report

Abstract: Okayama (2021) Strongyloides stercoralis colitis in a patient positive for human T-cell leukaemia virus with rheumatoid arthritis during an anti-rheumatic therapy: a case report,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…However, there is little information on strongyloidiasis in patients undergoing biological treatment. Most of the published cases are associated with the use of anti-TNF therapy (etanercept [ 42 ], infliximab [ 43 ], adalimumab [ 44 ] or golimumab [ 45 ], and attributed to the accumulation of circulating CD4 T helper type 1 lymphocytes, with a corresponding decrease in T helper type 2 cells [ 46 ]. A smaller number of cases has been reported in patients receiving monoclonal antibodies against IL-6R (tocilizumab) [ 47 ], anti-CD20 (rituximab) [ 48 ] or anti-CD52 (alentuzumab) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information on strongyloidiasis in patients undergoing biological treatment. Most of the published cases are associated with the use of anti-TNF therapy (etanercept [ 42 ], infliximab [ 43 ], adalimumab [ 44 ] or golimumab [ 45 ], and attributed to the accumulation of circulating CD4 T helper type 1 lymphocytes, with a corresponding decrease in T helper type 2 cells [ 46 ]. A smaller number of cases has been reported in patients receiving monoclonal antibodies against IL-6R (tocilizumab) [ 47 ], anti-CD20 (rituximab) [ 48 ] or anti-CD52 (alentuzumab) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hashiba et al reported a case of HTLV-1-positive RA patients who developed S. stercoralis colitis after administration of a TNF inhibitor [ 77 ]. Recently, a HTLV-1 RA cohort study found a higher incidence of serious infections requiring hospitalization in HTLV-1-positive RA patients than in HTLV-1-negative RA patients [ 68 ].…”
Section: Are There Any Differences In Clinical Features Between Htlv-...mentioning
confidence: 99%
“…In recent times, it has been observed that there is an increased risk of disseminated strongyloidiasis in patients with RA, taking immune system suppressing therapies [27][28][29]. A study in Turkey has identified patients with RA as being more at risk of developing strongyloidiasis than patients suffering from other immune-deficiency syndromes living in areas where strongyloid infections are endemic [30].…”
mentioning
confidence: 99%